An analysis of frequency events in Great Britain - Samuel Homan; Solomon Brown (Energy Reports, 2020)
With increasing penetration of wind and solar generation on electricity grids around the world, concerns are being raised about the effect this has on system stability. One measure of system stability is the volatility of the grid frequency. In this paper, an analysis is performed using one second resolution frequency data from Great Britain. We demonstrate that the number of frequency events has increased dramatically in the last couple of years, which coincides with the rapid increase in renewable penetration (wind and solar). We further demonstrate that the number of times the frequency is too high, corresponding to periods of more generation than demand, occurs roughly twice as often as when the frequency is too low. The different types of events (high and low) occur, on average, at different times in the day. The change in event severity and correlation between rate of change of frequency and settlement period boundaries is also presented. This study provides a useful insight into the state of stability of the electricity grid in Great Britain and when the system is at its most vulnerable.